A comparative analysis of sarcopenia screening methods in Thai people with type 2 diabetes mellitus in an outpatient setting - Ornpicha Laohajaroensombat; Thanapat Limpaarayakul; Nattapol Sathavarodom; Apussanee Boonyavarakul; Parinya Samakkarnthai (BMC Geriatrics)
Abstract Background Type 2 Diabetes Mellitus (T2DM) is closely linked with sarcopenia. The lack of validated, easy, and effective sarcopenia screening tools for people with T2DM may result in underdiagnosis, delayed interventions, and worsening outcomes. This study evaluated and compared the diagnostic accuracy of various sarcopenia screening tools in T2DM outpatients. Methodology A cross-sectional study was conducted on 329 people with T2DM at Phramongkutklao Hospital, Thailand, between December 2023 and November 2024. This study compared eight sarcopenia screening tools. The Asian Working Group for Sarcopenia 2019 (AWGS 2019) criteria served as the reference standard. Sensitivity, Specificity, and diagnostic accuracy were evaluated using receiver operating characteristic (ROC) curve analysis. The optimal cutoffs were identified with the Youden index. Results The prevalence of sarcopenia was 23.7%. Calf circumference showed the highest diagnostic accuracy at standard cutoff (AUC: 0.892), with optimised cutoff points of < 37.0 cm for males and < 36.0 cm for females, and achieved high sensitivity (90.1% for males, 91.1% for females) with acceptable specificity (77.2% for males, 67.8% for females). Neck circumference demonstrated diagnostic utility (AUC: 0.741) with proposed thresholds of < 39.5 cm (males) and < 36.5 cm (females), yielding moderate sensitivity (69.7% for males, 82.2% for females) and acceptable specificity (78.9% for males, 62.6% for females). Questionnaire-based tools showed limited diagnostic accuracy with SARC-CalF performing the best (AUC: 0.789, sensitivity: 48.7%, specificity: 93.2%). Among physical performance tests, handgrip strength was the most accurate (AUC: 0.716), although these tests generally exhibited high sensitivity, but lower specificity. Conclusion Calf circumference was the most effective screening tool for sarcopenia in people with T2DM. Neck circumference emerged as a promising alternative at optimal cutoff values, offering a simple, novel and practice screening tool option. These findings support the implementation of anthropometric measures for sarcopenia screening in clinical settings, particularly in outpatient care.